Portraits & Signaturen : 81 Künstler der documenta 6 (Kassel: [s.n.], 1977)
Abramovic, Marina ; Acconci, Vito ; Antonakos, Stephen ; Aycock, Alice ; Badura, Michael ; Bartlett, Jennifer ; Baumgartl, Monika ; Beuys, Joseph ; Bohnen, Blythe ; Brigham, Joan ; Brisley, Stuart ; Burgess, David L. ; Casdin-Silver, Harriet ; Christo ; Cohen, Harold ; Davis, Douglas ; Earls, Paul ; Fleischner, Richard ; Freyer, Achim ; Geissler, Michael ; Girke, Raimund ; Gonschior, Kuno ; Gramse, Tom ; Graubner, Gotthard ; Grosvenor, Robert ; Hall, Nigel ; Haraguchi, Noriyuki ; Head, Tim ; Heisig, Bernhard ; Hofkunst, Alfred ; Isenrath, Hans-Paul ; Jonas, Joan ; Karavan, Dani ; Korot, Beryl ; Kounellis, Jannis ; Kovacs, Attila ; Kubota, Shigeko ; Lakner, Laszlo ; Lang, Nikolaus ; Zeniuk, Jerry ; Levine, Les ; de Maria, Walter ; Matta-Clark, Gordon ; Miralda, Antoni ; Moser, Mike ; Muntadas, Antoni ; Nannucci, Mauricio ; Nesjar, Carl ; Neuhaus, Max ; Nierhoff, Ansgar ; Nonas, Richard ; Oppermann, Anna ; Pacileo, Dolores ; Paik, Nam June ; Pezold, Friederike ; Poirier, Anne & Patrick ; Potts, Don ; Pozzi, Lucio ; Reineking, James ; Reuter, Hans Peter ; Rinke, Klaus ; Ruthenbeck, Reiner ; Schmidt-Heins, Barbara ; Schmidt-Heins, Gabriele ; Schuler, Alf ; Serra, Richard ; Shapiro, Joel ; Sharits, Paul ; Sina, Alejandro ; Singer, Michael ; Sonfist, Alan ; Staeck, Klaus ; Titus-Carmel, Gérard ; Trakas, George ; Ulay ; Viola, Bill ; Vostell, Wolf ; Walther, Franz Erhard ; von Windheim, Dorothee ; Winner, Gerd
geboorteplaats en -datum, signatuur per kunstenaar
Duits
boek